Effectiveness of Autogenic Relaxation Therapy for Managing Mood Swings in Adolescent Girls with Premenstrual Syndrome - Hidayati, Ratna; Sri Astutik, Wahyu; Nita Ludyanti, Laviana (The Indonesian Institute of Science and Technology Research, 2025)
Premenstrual Syndrome (PMS) is associated with mood instability in adolescents, affecting emotional well-being and daily functioning. Non-pharmacological interventions, such as autogenic relaxation, may help manage these fluctuations. This study examined the effect of autogenic relaxation therapy on mood changes in 88 female adolescents at SMP Negeri 1 Pare, Kediri Regency, using a one-group pretest–posttest pre-experimental design. Mood was assessed with the Four Dimensions Mood Scale (FDMS) and analyzed using the Wilcoxon Signed-Rank test. Before the intervention, most participants (61.4%) reported negative mood. After autogenic relaxation, the majority (52.3%) shifted to the positive mood category, with statistically significant improvement (p < 0.001). These results suggest that autogenic relaxation promotes emotional regulation through focused attention and controlled breathing, supporting a physiological relaxation response. Autogenic relaxation appears to be a simple, accessible, and cost-effective method for managing PMS-related mood disturbances in adolescents. However, the absence of a control group and limited demographic scope warrant caution. Future studies with controlled designs and diverse populations are recommended.